GENOMIC COMPARISON AMONG THREE ARABIDOPSIS SPECIES REVEALED HEAVY METAL RESPONSIVE GENES - S. M. Jazayeri; L. C. García Cruzatty; R. Villamar-Torres (Journal of Animal and Plant Sciences, 2019)
Arabidopsis is the ever most well-known plant model. Publishing genome of A. thaliana has restructured biological sciences towards more knowledge on multi and interdisciplinary researches based on genomic data. Eleven approved species of Arabidopsis were classified into 4 groups. Despite of its importance in biology, only three Arabidopsis species genomes are available. Genomes, proteins and gene models in three Arabidopsis species including A. halleri, A. lyrata and A. thaliana were compared. Genomic comparison disclosed 80-90 % of similarity for proteins and gene models among three species. The clustered protein sets showed 79% of common orthologue proteins among three species. Transcript pairwise comparisons among three species showed a similarity range of 82-92%. Twenty-six species-specific clustered proteins related to heavy metal response are highlighted in A. halleri. They function in transport, phytochelat, protein degradation, cell wall formation, detoxification and signaling.
Keywords: Arabidopsis; genes; genomic comparison; heavy metal; tolerance